Entry into New Niches: The Effects of Firm Age and the Expansion of Technological Capabilities on Innovative Output and Impact - KOTHA, Reddi (Institutional Knowledge at Singapore Management University, 2011)
We provide evidence that young firms systematically differ from older firms in their innovative output when they enter ‘new to the firm’ technological niches. We analyze data from 128 biotechnology firms since their inception and track these firms over time. Our analyses reveal that the organizational age at which the firm branches into new technological niches significantly influences its innovative activity. We refine the focus of the extant literature by separately examining the effects of branching on the quantity of innovative output and the impact that this output has on the technology domain. Subsequent to branching into new niches, we find that older firms have a higher quantity of output than their younger counterparts, whereas young firms tend to outpace their older rivals with higher impact. We discuss the implications of these findings for the literature on dynamic capabilities and entrepreneurship.